2018
DOI: 10.3390/ijms19103151
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Upregulation of Cleaved-Caspase-3 Associated with Chronic Myelin Pathology and Microvascular Reorganization in the Thalamus after Traumatic Brain Injury in Rats

Abstract: Traumatic brain injury (TBI) is associated with long-term disabilities and devastating chronic neurological complications including problems with cognition, motor function, sensory processing, as well as behavioral deficits and mental health problems such as anxiety, depression, personality change and social unsuitability. Clinical data suggest that disruption of the thalamo-cortical system including anatomical and metabolic changes in the thalamus following TBI might be responsible for some chronic neurologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 97 publications
3
9
0
Order By: Relevance
“…Oxidative stress and neuroinflammation are the major hallmarks of post-brain injury consequences and neuropsychiatric disturbances [18]. Excessive reactive oxygen species (ROS) in the brain can cause damage to the enzymes, nucleic acid, and disruption of structural protein [19,20,21]. Several lines of studies have demonstrated elevated ROS and neuroinflammation in brains after brain injuries [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress and neuroinflammation are the major hallmarks of post-brain injury consequences and neuropsychiatric disturbances [18]. Excessive reactive oxygen species (ROS) in the brain can cause damage to the enzymes, nucleic acid, and disruption of structural protein [19,20,21]. Several lines of studies have demonstrated elevated ROS and neuroinflammation in brains after brain injuries [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…It seems probable that TBI directly and indirectly damages cortical and subcortical structures that are associated with visual processing. Animal models of TBI have shown altered thalamic myelin integrity (27) and even mild TBI has been shown in some cases to contribute to excitotoxic injury with delayed cell death in the cortex, thalamus, and subcortical white matter tracts (28). Some authors hypothesize that disrupted thalamocortical circuits contribute to some of the symptoms of TBI (27), and in theory this might also contribute to VS symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…TBI can lead to chronic neurodegeneration and long‐term neurological deficits 28‐30 . For example, neurological severity scores, rotarod latency, impairments of cognitive function in Y or Water maze, 31,32 foot faults in motor function test, 33 and forelimb asymmetry 32 were increased and lasted up to 28‐35 days after CCI in mice.…”
Section: Discussionmentioning
confidence: 99%